Forensic Diagnostics of the Circumstances of Digital Video and Audio Production: Analytical Review - M. A. Voznyuk; Yu. A. Denisov (Теория и практика судебной экспертизы, 2017)
The analytical review examines the issues of forensic investigation into the circumstances of production of digital video and audio recordings. The paper presents the organization and lines of inquiry in forensic analysis of video and audio evidence, computer forensics, forensic linguistics, and psychological evaluation established in the system of forensic science organizations of the Russian Ministry of Justice by 2013–2016. The analysis covers the issues of independent or integrated application of the listed types of special knowledge in order to meet the discipline-specific and comprehensive objectives of determining the circumstances of video/audio production. General strategies and types of forensic diagnostics of production circumstances are discussed without too much emphasis on the methodological minutiae of every stage of the investigation.